The Effect of Replacement of Natural Gravel with Recycled Aggregate on Concrete Compressive Strength (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The increasing demand for natural aggregates in concrete production has raised concerns about the shortage of natural resources and environmental pollution. This research explores the possibility of replacing natural gravel with recycled aggregate obtained from crushed mosaic tiles in concrete mixtures. The study aims to evaluate the use of construction and building waste in concrete production as an eco-friendly alternative to conventional aggregates.Four experimental concrete mixtures were designed to examine the effect of replacing natural gravel with crushed mosaic tiles. The first mixture served as a reference mix, containing 100% natural gravel. The second mixture included 25% crushed tiles and 75% natural gravel. The third mixture consisted of equal amounts of both materials (50% each), while the fourth mixture completely replaced natural gravel with 100% crushed tiles.The main goal of this study is to find the best replacement ratio that ensures good concrete properties while helping the environment. By using recycled materials, this research helps reduce environmental impact, decrease construction waste, and save natural resources. The results are expected to provide useful information on the possibility of using alternative materials in concrete production, supporting eco-friendly building practices.